Application of a simplified value analysis methodology (VAM-2P) and CAD/CAE tools to Agro-industrial product redesign: Harvesting trolley case study - Robles-López, Juan J.; González-Yebra, Óscar; Aguilar, Fernando J.; Aguilar, Manuel A. (Springer Nature, 2025)
The agri-food sector is an area where the design component can be considered to play a minor role as a non-technological driver of innovation. Un-like sectors like graphic design and communication, intellectual property protec-tion is limited in industrial design, hindering innovation. To address this gap, the presented proposal advocates for an educational initiative to cultivate interest in industrial design among engineering students, following the UNE 144001 IN standard. The proposed methodology, called Value Analysis Methodology in 2 phases (VAM-2P), simplifies value analysis to prompt quick idea generation without focusing on economic aspect. On a first step, the students identify user needs in relation with the object to be redesigned. After that, CAD/CAE tools are used to generate 3D models and evaluate solutions against technical constraints. A case study on eco-design for a harvesting trolley illustrates this approach, em-phasizing the use of SolidWorks 3D CAD® software to assess environmental impacts. This initiative aligns with Sustainable Development Goal 4 (SDG 4) and Target 4.4 of 2030 Agenda for Sustainable Development, which aims to increase the acquisition of relevant skills needed to promote entrepreneurship among young people and adults.
Keywords: Diseño industrial - Estudio y enseñanza; Design-driven innovation; Higher education; Value analysis; CAD/CAE tools; Sustainability; Industrial design training; Engineering projects